PENYULUHAN KESEHATAN, PEMERIKSAAN TELUR CACING, DAN HEMOGLOBIN PADA PENGRAJIN GENTENG DI KECAMATAN KEDIRI, KABUPATEN TABANAN - I Gusti Agung Dewi Sarihati; I Wayan Merta (Jurnal Pengabmas Masyarakat Sehat (JPMS), 2020)
STH (soil transmited helmint) such as Ascaris lumbricoides, Trichuris trichura and Hookworm are intestinal nematodes which are transmitted through the soil. Worm disease is one of the causes of anemia, a result of malnutrition and the presence of bleeding that is not visible in people with helminthiasis. This community service aims to provide services to tile craftsmen in Kediri District, Tabanan in order to reduce the incidence of helminthiasis and its effect on hemoglobin levels.This community service is carried out in the form of health counseling, examination of worm eggs, and hemoglobin (Hb) and its handling if found to be positive for worm eggs and Hb levels below normal. Examination results show the presence of worm eggs in 32% of tile craftsmen and hemoglobin levels below normal by 34%. Craftsmen infected with helminthiasis as well as those who have Hb levels below normal have received good treatment from servants and cooperation with the Health Center I Kediri.Tile craftsmen are advised to use personal protective equipment to prevent contact with soil containing infective eggs. Health centers to continue to run health promotion and monitor people with worms.Keywords: worm eggs, hemoglobin, tile craftsman.